2015
DOI: 10.1111/hae.12685
|View full text |Cite
|
Sign up to set email alerts
|

New associations: INFG and TGFB1 genes and the inhibitor development in severe haemophilia A

Abstract: This suggests that polymorphisms in INFG and in TGFB1 genes are related to risk of developing inhibitor, and could contribute to a genetic profile of the individual HA for the risk of inhibitors development to FVIII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…As known, cytokines are more or less directly involved in the antibody-mediated immune responses [26,27]. In patients with autoimmune disease, polymorphisms in the immune response genes were found to be associated with antibody formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As known, cytokines are more or less directly involved in the antibody-mediated immune responses [26,27]. In patients with autoimmune disease, polymorphisms in the immune response genes were found to be associated with antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…The development of FVIII inhibitor is the main complication of replacement therapy in patients with haemophilia A. Indeed, the immunomodulatory cytokine genes have been related to the risk of development of alloantibodies in several studies, mainly in HA with severe form [26]. For instance, polymorphic variants at IL-2 gene was associated with several autoimmune conditions including type 1 diabetes, rheumatoid arthritis, multiple sclerosis and bleeding disorders [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes that play an important role in the antibody‐mediated immune response may affect FVIII inhibitor production . Polymorphisms in immune response‐related genes have been suggested in various studies and cohorts as important genetic risk factors for inhibitor formation . Some gene polymorphisms, such as those in the IL10, TNFa and CTLA4 genes, have been suggested as contributing determinants of inhibitor risk .…”
Section: Introductionmentioning
confidence: 99%
“…5 Polymorphisms in immune response-related genes have been suggested in various studies and cohorts as important genetic risk factors for inhibitor formation. [6][7][8] Some gene polymorphisms, such as those in the IL10, TNFa and CTLA4 genes, have been suggested as contributing determinants of inhibitor risk. [9][10][11] Lu et al 12 found that a haplotype of IL10 was associated with inhibitor risk in Chinese HA patients.…”
mentioning
confidence: 99%